The Biological Inferiority of the Undeserving Poor - Michael B. Katz (Social Work & Society, 2013)
For most of recorded history, poverty reflected God's will. The poor were always with us. They were not inherently immoral, dangerous, or different. They were not to be shunned, feared, or avoided. In the late eighteenth and early nineteenth centuries, a harsh new idea of poverty and poor people as different and inferior began to replace this ancient biblical view. In what ways, exactly, are poor people different from the rest of us became - and remains - a burning question answered with moral philosophy, political economy, social science, and, eventually, biology. Why did biological conceptions of poverty wax and wane over the last century and a half? What forms have they taken? What have been their consequences?